Dinamika Jual Beli Dan Potensi Riba Era Digital Perspektif Al-Qur’an - Ashabul Kahfi,; Achmad Abubakar,; Rahmi Damis, (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to analyze the concept of buying and selling and the prohibition of usury in the Qur'an and its application to technology-based economics. This type of research is included in the type of qualitative research with a qualitative descriptive model. The analysis technique used in this research is content analysis technique. The results show that the Qur'an allows buying and selling as long as it fulfills sharia principles such as justice and transparency, while usury in its various forms is legally prohibited because it does not fulfill the elements of justice and humanity. The digital economy provides new marketing opportunities through platforms such as e-commerce and fintech, but presents new challenges such as innovative business models that must be assessed for Shariah compliance. Ensuring Shariah compliance requires fatwas from authorized institutions and cooperation among scholars on every new product or service that emerges in today's digital era.